Morphological and vascular evidence of glaucomatous damage in myopic guinea pigs with scleral crosslinking - Lei Guo; Jun Tao; Ziqi Guo; Yang Tong; Shichao Chen; Xin Zhao; Rui Hua (Scientific Reports, 2024)
Abstract Guinea pigs are often used as models for myopia studies. However, the imaging structure and vasculature of the optic nerve head (ONH) in guinea pigs are tentative. This study investigated morphological parameters and vascular characteristics of the ONH in guinea pigs with form deprivation (FD) myopia before and after scleral crosslinking (CXL), using optical coherence tomography (OCT) and OCT angiography (OCTA). Refractive error, axial length (AL), intraocular pressure (IOP), and OCT-based structural parameters of the ONH were measured at baseline and 3 weeks after the FD + CXL procedure in guinea pigs. The 88 guinea pigs analysed in this study were aged 3 (n = 29), 4 (n = 51), and 5 (n = 8) weeks. The IOP, AL, average and vertical cup-to-disc ratio (C/D), circumpapillary retinal nerve fibre layer, disc area, and cup volume increased at 3 weeks compared to baseline values (all p < 0.001). The refractive error and rim area decreased at 3 weeks compared to baseline values (all p < 0.001). After adjustment for age, IOP was correlated positively with average C/D (p = 0.039) and negatively with rim area (p = 0.009). The severity of blood signal defects was positively associated with the average C/D at 3 weeks (p = 0.027). These findings may facilitate further research on myopia using guinea pigs.